A New Approach to Concavity Fuzzification - Ibtesam Alshammari; Azza M. Alghamdi; A. Ghareeb (Journal of Mathematics)
In this paper, we introduce a more general approach to the fuzzification of fuzzy concavity. More specifically, the degree of L,M-fuzzy concavity is introduced and characterized as a generalization of L-concave structure and L,M-fuzzy concave structure. Based on that, the degree of L,M-fuzzy concavity preserving and L,M-fuzzy concave-to-concave of a function are defined. Some properties and relationships between the degree of L,M-fuzzy concavity preserving and L,M-fuzzy concave-to-concave functions are discussed.